Internal and external quality control in the medical microbiology laboratory (2018)
Culture media play a very important role in bacteriology as they are used in the isolation, identification and antimicrobial susceptibility testing. It is essential that the quality of media be safeguarded to have a successful microbiology laboratory. Microorganisms usually show typical morphological appearance and properties on solid media. Variations in the composition of the medium may alter this appearance and properties. There is therefore a need to ensure good quality media, which is capable of giving satisfactory results by ensuring a proper quality management system. Often times, majority of laboratories prepare their media for routine diagnostics and research purposes. Therefore, it is essential that certain parameters of media are checked thoroughly before they are considered suitable for laboratory use. Control methods are discussed in details in this report.